PERANAN POLA ASUH ORANG TUA TERHADAP KEMANDIRIAN PERSONAL HYGIENE PADA ANAK AUTIS DI SD - WAHYU DEWI, KARINA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Parents were the ones who had the most important role in caring, guiding, and directing the children to become independent. Therefore, the parents would apply good parenting style to nurture their autism children in order to reach independence included personal hygiene independence. The personal hygiene independence was an individual ability not to depend on other people in doing personal hygiene activity. Based on the observation which had been done in SDN Percobaan Surabaya, three autism children were less realizing the importance of self hygiene. A child whose teeth appeared yellow and two others had a habit i.e. after cleaning the nose dirt they would absorb it so it required to be observed the role of parenting style toward personal hygiene independence to autism children in SDN Percobaan Surabaya. This research had purpose to describe the parenting style of autism children in SDN Percobaan Surabaya, to describe personal hygiene independence to autism children in SDN Percobaan Surabaya, and to describe the role of parenting style toward personal hygiene independence to autism children in SDN Percobaan Surabaya. This research used qualitative approach with descriptive method. The technique of data collection was done by interview and observation toward 5 parents, 5 autism children, and 2 siblings of 2 autism children. The technique of data analysis in this research used the step of data condensation, data display, and conclusion drawing / verifying suitable with the analysis model of Miles, Huberman, and Saldana. This research result indicated that a whole or 100% parents of autism children who consisted of 5 parents of 5 autism children in SDN Percobaan Surabaya applied authoritative parenting style as the dominant and authoritarian parenting style was as the secondary parenting style in one caring at once. In personal hygiene independence, the independent autism children in SDN Percobaan Surabaya were 3 children (60%), and less independent autism children were 2 children (40%). So it could be concluded that the parenting style gave great role toward the personal hygiene independence to autism children in SDN Percobaan Surabaya. The role of authoritative parenting style was the parents helped personal hygiene activity of the children physically and verbally, to teach the children doing personal hygiene activity, to assist the children doing personal hygiene activity, and to remind the children when they did not do personal hygiene activity yet while in authoritarian parenting style, the parents compelled the children in order to be able to do personal hygiene activity by themselves, to order each step in personal hygiene activity, and to scold the children when they did not soon to do personal hygiene activity on time.   Keywords: parenting style, personal hygiene independence